Albiglutide for the treatment of type 2 diabetes mellitus: An integrated safety analysis of the HARMONY phase 3 trials. (April 2017) - Ahrén, Bo; Carr, Molly C.; Murphy, Karen; Perkins, Christopher; Rendell, Marc; Mallory, Jason; Wilson, Timothy; Johnson, Susan
Highlights: Integrated safety analysis from albiglutide phase 3 trials of up to 3 years' length. Frequency of overall AEs was similar between albiglutide and pooled comparators. Renal and cardiac function were similar between albiglutide and pooled comparators. Specific AEs with similar frequencies included nausea, vomiting, and hypoglycaemia. Injection-site reaction and diarrhoea AEs were more frequent with albiglutide. Abstract: Aims: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) stimulate the incretin system and lower glycaemic parameters in type 2 diabetes mellitus (T2DM). This analysis of clinical studies of up to 3 years evaluated the safety of albiglutide, a GLP-1 RA, in people with T2DM. Methods: Integrated safety analysis included seven phase-3 T2DM studies of albiglutide compared with placebo and/or active comparators (a dipeptidyl peptidase-4 inhibitor, GLP-1 RA, insulin, sulphonylurea, and thiazolidinedione). Results: Studies of 32 months (HARMONY 7), 1 year (HARMONY 6), and 3 years (HARMONY 1–5), reported similar rates of adverse events (AEs) (84.8%, 82.3%), and serious AEs (13.1%, 12.9%) between albiglutide and all comparators, respectively. AEs that did not differ between the groups included symptomatic or severe hypoglycaemia as well as nausea (12.0%, 11.3%) and vomiting (5.3%, 4.7%) for albiglutide and all comparators, respectively. According to the Medical Dictionary for Regulatory Activities preferred terms, only diarrhoea (13.7%, 9.9%), injection-site reaction (9.0%, 2.0%), and peripheral oedema (4.5%, 6.8%) had at least 2% difference between the albiglutide and all-comparator groups. In a similar integrated analysis, pancreatitis occurred more often with albiglutide (0.3%, 0.1%). Renal and cardiac function did not differ between the two groups. Conclusions: In an integrated analysis of seven phase 3 clinical trials, albiglutide-treated patients experienced frequencies of AEs (including cardiovascular and renal) similar to the all-comparators group treated with other T2DM medications or placebo. Albiglutide treatment was associated with higher rates of diarrhoea and injection-site reactions, but not increased nausea and vomiting, versus all comparators.